2017
DOI: 10.1097/spc.0000000000000262
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine for cancer pain: what is the evidence?

Abstract: Ketamine is an N-methyl-D-aspartate receptor antagonist that at low-dose has effective analgesic properties. In cancer pain, ketamine is usually prescribed as adjuvant to opioid therapy when pain becomes opioid resistant or when neuropathic pain symptoms dominate the clinical picture. A literature search revealed four randomized controlled trials that examined the benefit of oral, subcutaneous or intravenous ketamine in opioid refractory cancer pain. None showed clinically relevant benefit in relieving pain or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Still, despite a lack of evidence for other indications, ketamine remains abundantly used clinically for treatment of acute and chronic cancer and non-cancer pain. In fact, numerous case reports, case series, and open-label studies show ketamine efficacy in the amelioration of acute and chronic pain 5 , 48 , 49 . Reasons for the apparent discrepancy in efficacy in RCTs versus open-label treatments are difficult to give.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Still, despite a lack of evidence for other indications, ketamine remains abundantly used clinically for treatment of acute and chronic cancer and non-cancer pain. In fact, numerous case reports, case series, and open-label studies show ketamine efficacy in the amelioration of acute and chronic pain 5 , 48 , 49 . Reasons for the apparent discrepancy in efficacy in RCTs versus open-label treatments are difficult to give.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for the apparent discrepancy in efficacy in RCTs versus open-label treatments are difficult to give. Various, often interacting, factors may play a role herein 5 , 48 : (i) One important issue is the duration of treatment. We previously showed that prolonging the duration of intravenous ketamine treatment to 10–100 hours increases the probability of therapeutic success 46 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations